Transitioning from Low-Income Growth to High-Income Growth : Is There a Middle Income Trap? - Bulman, David; Eden, Maya; Nguyen, Ha (World Bank Group, Washington, DC, 2014)
Is there a "middle income trap"? Theory suggests that the determinants of growth at low and high income levels may be different. If countries struggle to transition from growth strategies that are effective at low income levels to growth strategies that are effective at high income levels, they may stagnate at some middle income level; this phenomenon can be thought of as a "middle income trap." This paper does not find evidence for (unusual) stagnation at any particular middle income level. However, it does find evidence that the determinants of growth at low and high income levels differ. These findings suggest a mixed conclusion: middle-income countries may need to change growth strategies to transition smoothly to high-income growth strategies, but this can be done smoothly and does not imply the existence of a middle income trap.